Body composition and lung cancer-associated cachexia in TRACERx - Al-Sawaf, Othman (Nat Med, 2023)
Cancer-associated cachexia (CAC) is a major determinant of morbidity and mortality in patients with non-small cell lung cancer (NSCLC). Key features of CAC include alterations in body composition and body weight. Here, we explore the association between body composition and body weight with survival and delineate possible biological processes and mediators that contribute to the development of CAC. Computed tomography-based (CT) body composition analysis of 651 patients in TRACERx suggested that patients with low skeletal muscle or adipose tissue area at the time of lung cancer diagnosis, represented by the bottom 20(th) percentile, had significantly shorter lung cancer-specific survival (LCSS) and overall survival (OS). This finding was validated in 420 patients in the independent Boston Lung Cancer Study. In a longitudinal subset of 272 patients in TRACERx who experienced disease relapse, loss of adipose tissue, skeletal muscle, or body weight in the interval between diagnosis and relapse, was significantly associated with shorter LCSS and OS. Patients with one or more features encompassing loss of adipose or muscle tissue, or BMI-adjusted weight loss according to specific thresholds were classified as having developed CAC and were found to have distinct tumour genomic and transcriptomic profiles compared with patients who did not develop such features at relapse. Primary NSCLCs from patients in the CAC group were characterised by enrichment of inflammatory signalling and epithelial-mesenchymal transitional pathways, and differentially expressed genes upregulated in these tumours included cancer-testis antigen MAGEA6 and matrix metalloproteinases, such as ADAMTS3. In an exploratory analysis of putative circulating cachexia mediators performed in a subset of 256 baseline and relapse plasma samples from TRACERx, proteomic analysis revealed a significant association between circulating GDF15 and loss of body weight, skeletal muscle, and adipose tissue at relapse, supporting the potential therapeutic relevance of targeting GDF15 in the management of CAC.